Penanaman karakter disiplin dan tanggung jawab melalui penegakan tata tertib sekolah di SMK Negeri 1 Gesi - Utomo, Randi Seno Yudho; Setyadi, Yulianto Bambang (Jurnal Pendidikan Karakter, 2022)
This study aims to describe the cultivation of the character of discipline and responsibility through enforcing school rules, as well as the inhibiting factors, driving factors, and the role of parents in instilling these characters at SMK Negeri 1 Gesi, Sragen Regency. This is qualitative descriptive research with a case study design. Collecting data using observation, interviews, and documentation techniques. Data analysis used the interactive analysis technique of the model of Miles and Huberman. The results showed that the cultivation of the character of discipline and responsibility at SMK Negeri 1 Gesi was carried out by getting into the habit of arriving on time, wearing complete and neat uniforms, obeying regulations, carrying out picket duties regularly, guarding and maintaining educational facilities, and participating in school activities. Inhibiting factors include road access and obstacles to vehicles, lack of attention from parents, influence of other students, as well as being lazy and arriving late on purpose. The driving factors include sanctions, monitoring and implementation of inspections, the existence of student pocket books, and the attention of teachers and fellow picket groups to create a clean and comfortable learning atmosphere. The role of parents includes getting used to time discipline, setting an example of ethical dress, and getting used to obeying rules.